An innovative approach for natural gas liquefaction using a mixed-multi-component-refrigerant - Ismail, N.H.; Omar, M.N.; Ishak, M.S.A; Yahaya, N.Z.; Khalid, K.A.A.; Mohd Ab Halim, Mohd Firdaus (2023)
The natural gas liquefaction is the most expensive and energy-intensive phase in the natural gas-to-liquefied natural gas-to-natural gas chain. In addition, this region has the biggest development potential. As a result, numerous LNG production methods have been developed and are deployed at export facilities around the world. The goal of this study is to describe and assess an innovative approach for mixed-refrigerant (MR) LNG method. The authors have dubbed this technique the MR-X approach. The MR-X process was developed based on the globally proven liquefaction technology C3MR and its large-scale successor AP-XTM (which offers many benefits and flexibility), but with a novel precooling phase construct. In pre-cooling and liquefaction phases, the refrigerant is a combination of methane, nitrogen, propane, ethane, butane, and isobutane. The paper investigates the creation of the MR-X technology, as well as its modelling, energy, and exergy investigations.